1995
DOI: 10.1074/jbc.270.28.16569
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of a cDNA for a Mammalian Type III Iodothyronine Deiodinase

Abstract: The type III iodothyronine deiodinase metabolizes the active thyroid hormones thyroxine and 3,5,3'-triiodothyronine to inactive compounds. Recently, we have characterized a Xenopus laevis cDNA (XL-15) that encodes a selenoprotein with type III deiodinase activity (St. Germain, D.L., Schwartzman, R., Croteau, W., Kanamori, A., Wang, Z., Brown, D.D., and Galton, V.A. (1994) Proc. Natl. Acad. Sci. U.S.A. 91, 7767-7771). Using the XL-15 as a probe, we screened a rat neonatal skin cDNA library. Among the clones iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 181 publications
(71 citation statements)
references
References 26 publications
3
65
0
3
Order By: Relevance
“…Type 2 deiodinase expression in rodent heart is much lower than in human heart (Croteau et at., 1996), therefore rodents are not considered a suitable model for human D2 regulation. Cardiac D2 mRNA and activity in mouse and rats has, however, been demonstrated to respond to changes in thyroid hormone levels induced by hypothyroidism provoked by methimazol treatment (Wagner et al, 2003) or iodine deficiency (Lavado-Autric et al, 2013) and attenuated by T3 administration (Wagner et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 deiodinase expression in rodent heart is much lower than in human heart (Croteau et at., 1996), therefore rodents are not considered a suitable model for human D2 regulation. Cardiac D2 mRNA and activity in mouse and rats has, however, been demonstrated to respond to changes in thyroid hormone levels induced by hypothyroidism provoked by methimazol treatment (Wagner et al, 2003) or iodine deficiency (Lavado-Autric et al, 2013) and attenuated by T3 administration (Wagner et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Poly(A) + RNA was isolated from the total RNA as described previously (18). Northern analysis was carried out as described previously using the NS43-1 rat D3 cDNA as a probe (19). Hybridization was conducted at 42°C with final washes at 55°C (18).…”
Section: Methodsmentioning
confidence: 99%
“…The metabolic activation (Behne et al, 1990;Arthur et al, 1990;Davey et al, 1995), as well as degradation of thyroid hormones (Croteau et al, 1995), were shown to depend on selenium-containing deiodinases. Most surprisingly, selenium was also discovered in a well-documented enzyme of basic metabolic relevance, in thioredoxin reductase (Tamura and Stadtman, 1996).…”
Section: Introduction: Some Historical Landmarksmentioning
confidence: 99%